Improving press machine efficiency using a TPM approach and Six Big Losses analysis - Supriyati, Supriyati; Wiyatno, Tri Ngudi (Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to improve the efficiency of press machines in the food manufacturing industry by implementing the Total Productive Maintenance (TPM) method and analyzing the Six Big Losses. The main issues identified include high downtime, excessive vibrations, and machine component failures, all of which negatively impact production efficiency. This research measures Overall Equipment Effectiveness (OEE) based on three key parameters: availability, performance, and quality. The results indicate that the average OEE is 84%, which falls below the 85% standard recommended by the Japan Institute of Plant Maintenance (JIPM). The primary causes of low efficiency are idling and minor stoppages (48%) and equipment failures (28%), both of which are influenced by a lack of preventive maintenance and errors in machine settings. A fishbone diagram analysis identifies the key factors contributing to inefficiency. To enhance machine effectiveness and reduce waste, a more optimized TPM implementation is recommended, focusing on Autonomous Maintenance and Preventive Maintenance. This study confirms that applying TPM and OEE can optimize production performance and improve the competitiveness of the manufacturing industry through enhanced maintenance systems and machine efficiency.